Aplikasi Citra WorldView-2 Untuk Pemetaan Batimetri Di Pulau Kemujan Taman Nasional Karimunjawa - Rahman, Waskito; Wicaksono, Pramaditya (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2019)
The Application of WorldView-2 Image for Bathymetry Mapping in Kemujan Island Karimunjawa National Park The development of remote sensing technology gives an opportunity to extract bathymetry information on the optically shallow water area. This was done by utilizing the reflectance of spectral bands with the ability to penetrate water body. The aim of this research is to map bathymetry of Kemujan Island using remote sensing empirical modeling.  Quickbird image was used in this study. It has four spectral bands namely blue, green, red and near infrared band. These bands were rationed and acquired 12 band ratios. In total, 120 samples were used to produce bathymetry model and 379 samples were used for validation. The models were created for up to the depth of 7 m.  The result showed that the model from band ratio of green and blue band produced the highest accuracy with R² of 0.632 and SE of 1.2 m. The result proved that blue band is the most effective band to be combined with other bands for band ratio input for bathymetry modeling.